Beyond GDP : Measuring Welfare and Assessing Sustainability - Fleurbaey, Marc and Blanchet, Didier (Oxford, Toronto Oxford University Press, 2013)
Is GDP a good proxy for social welfare? Building on economic theory, this book confirms that it is not, but also that most alternatives to it share its basic flaw, i.e., a focus on specific aspects of people's lives without sufficiently taking account of people's values and goals. A better approach is possible
Include Bibliography and Index
Keywords: Social policy -- Welfare economics -- Economic policy